Study of nutritional status and feeding practices in under five children from Solapur city - Jidge, Ashvini C.; Rokade, Hemlata G.; Rokade, Hemlata G.; Nadgire, Snehal S.; Nadgire, Snehal S. (International Journal Of Community Medicine And Public Health, 2022)
Background: In spite of various nutrition programs, burden of malnutrition is still high in India. Therefore, it is necessary to find out the gaps in community. Objective was to study the proportion of malnutrition and its association with some of the socio-demographic factors and also to study the trends of complementary feeding practices in children from 0 to 5 years attending UHTC OPD. Methods: This is a cross-sectional study conducted in 146 children under 5 years attending UHTC OPD during a study period of 2 months. Results: There were 70.55% of participants having malnutrition. About 15.75% children were severely acute malnourished. About 75.34% mothers received advice about breast feeding and complementary feeding. Exclusively breastfed infants were 48.63% and 52.05% infants were started complementary feeding on time. Only 25.34% were eating food from ≥4 groups and 74.65% children received <4 food groups. Conclusions: Efforts are needed to promote exclusive breastfeeding and age-appropriate complementary feeding among infants.